(3GdYbO GdOhdj GdEdcJQhfj GdeHQe YHQ GdEfJQfJ eY GdJQcjR Ydi YbO GdHjY GdOhdj ddHVGFY (B=s International e-contract concluded via internat wihe concentration on goods sale internationalcontract - (3fGUQ, MehOj eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2012)
(3HNUhU YbO GdHjY GdOhdj ddHVGFY fLO GJaGbjI ajjfG ef Cge GdCYeGd Ydi GdEWdGb GdgGOaI Edi JhMjO bhGYO GdbGfhf GdOhdj HNUhU gPG GdfhY ef GdYbhO GdefLRI ef bHd dLfI GdbGfhf GdJLGQj GdOhdj GdJGHYI defXeI GdCee GdeJMOI hGdJj TQY ajgG efP SfI (B1968 (3NdGd OhQJgG GdChdi GdJj CSaQJ YGe (B1972 (3Yf hVY GJaGbjJjf GdChdi JNU Jchjf GdYbO hGdKGfjI JNU BKGQg ZjQ Cfg de jcJH dgeG GdfLGM HSHH GdYOO GdVFjd ef GdOhd GdJj UGObJ YdjgeG HMLI Cf ZGdHjI GdOhd NGUI GdfGejI hHGdNUhU GdOhd GdCTJQGcjI efgG de JTGQc aj CYeGdgeG GdJMVjQjI GdJj WZJ YdjgG GdfRYI GdChQhHjI(B.s
(3GdCUd CWQhMI OcJhQGg(B- (3HETQGa GdCSJGP GdOcJhQ eYGTh YeGQ aj LGeYI JjRj hRh(B-(3GdLRGFQs
(3HHdjhLQGajI (B: (3UaMI (B555-607.s
Keywords: (3YbhO GdHjY (B((3bGfhf Ohdj(B)s; (3GdYbhO GdEdcJQhfjI (B((3bGfhf Ohdj(B)s